Putting a price tag on security: Subjective well-being and willingness-to-pay for crime reduction in Europe - Mattheus Brenig; Till Proeger (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
Using information on life satisfaction and crime from the European Social Survey, we apply the life satisfaction approach (LSA) to determine the relationship between subjective well-being (SWB), income, victimization experience, fear of crime and various regional crime rates across European regions, while controlling for potentially confounding socio-economic variables. We show that fear of crime, criminal victimization and the average regionally perceived fear of crime significantly reduce life satisfaction across Europe. Building upon these results, we quantify the monetary value of improvements in public safety and its valuation in terms of individual well-being. The loss in satisfaction for victimized individuals corresponds to 21,790 exteuro. Increasing an average individuals perception within his neighborhood from unsafe to safe yields a benefit equivalent to 12,700 exteuro. Our results regarding crime and SWB in Europe largely resemble previous results for different countries and other criminal contexts, whereby using the LSA as a valuation method for public good provision yields similar results as stated preference methods and considerably higher estimates than revealed preference methods.
Keywords: D10; H41; H56; I31; 330; crime rate; fear of crime; life satisfaction approach; subjective well-being; willingness-to-pay